PRUDENTIAL POLICY OF BANKS IN FINANCING INNOVATIVEECONOMIC DEVELOPMENT - Zavadska, Diana (Current Problems of Sustainable Development, 2026)
The article substantiates a scientific approach to banks’ prudential policy as an institutional regime that combines the containment of systemic risk with support for high-quality financing of innovative economic development. The relevance of the study is determined by Ukraine’s need for recovery, technological modernisation, and the development of energy-efficient and digital projects under conditions of war-related risks, strengthened regulatory requirements, and integration into the European financial area. The relationship between macroprudential policy, microprudential supervision, digital operational resilience, ESG risks, and banks’ innovative lending is revealed. The regulatory approaches of the BCBS, ESRB, EBA, and the National Bank of Ukraine to financial resilience, digital risks, operational resilience, and ESG-oriented risk management are systematised. An author’s model for coordinating prudential instruments in the system of financing innovative development is proposed. The model combines the stability of the banking sector, control of systemic risks, and the expansion of productive lending. Based on NBU data, an indicator-based assessment of the result-oriented block of the model is carried out. This assessment identified signs of high-quality credit recovery in the Ukrainian banking sector in 2024–2025, in particular growth in loans to business entities and SMEs, a decrease in the risk burden, improvement in the quality of the loan portfolio, and preservation of capital resilience.